1987
DOI: 10.1007/bf03007694
|View full text |Cite
|
Sign up to set email alerts
|

Technical Report The effect of pancuronium on the solubility of aqueous thiopentone

Abstract: In this study we identified the precipitate formed when pancuronium bromide (.oH 3.9) and sodium thiopentone (pH 10.6) potency, pulmonary vascular tone or the incidence of peripheral thrombophlebitis are unclear.Since a number of reaction products could result from combining solutions of thiopentone and pancuronium, we determined the composition of the precipitate and supernatant when these two drugs are combined. MethodsA commercial preparation (Abbott Laboratories) of 1 g of sodium thiopentone with 60 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Mivacurium, closest in pH to thiopentone shows the least precipitation compared with the other more acidic muscle relaxants. The precipitate for the reaction has been shown by UV spectrophotometry to be thiopentone acid, 4 and subsequent studies have shown that it is highly insoluble in human plasma (<0.1 mg mL −1 ), especially when compared with thiopental (700 mg mLl −1 ). 3 …”
Section: Discussionmentioning
confidence: 99%
“…Mivacurium, closest in pH to thiopentone shows the least precipitation compared with the other more acidic muscle relaxants. The precipitate for the reaction has been shown by UV spectrophotometry to be thiopentone acid, 4 and subsequent studies have shown that it is highly insoluble in human plasma (<0.1 mg mL −1 ), especially when compared with thiopental (700 mg mLl −1 ). 3 …”
Section: Discussionmentioning
confidence: 99%
“…We would like to draw attention to the precipitation in the iv line that may occur when muscle relaxants are injected (36). When thiopental (pH 11) is mixed with a nondepolarizing muscle relaxant (pH 4) a precipitation of insoluble thiopental crystals occurs (41,42). Animal studies have shown that these thiopental crystals cause lung emboli (41), which may cause bronchospasm due to the release of bronchoconstrictive mediators in the lung capillaries (2,36).…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Trial and error (lots of errors…) showed that precipitation may follow in any number of unlicensed drug mixtures with succeeding generations repeating the mistakes of their predecessors. 1,2 Naïvely, anesthetists may assume that the absence of crystals or of any other changes visible to the naked eye implies compatibility but this is not necessarily the case. Ever since it first became available for use in clinical practice, anesthetists have experimented with the addition of diluents and other drugs to the propofol formulation.…”
Section: Introductionmentioning
confidence: 99%
“…Older anesthetists may remember the crunch of precipitating thiopental caused by injecting succinylcholine into an un‐flushed cannula. Trial and error (lots of errors…) showed that precipitation may follow in any number of unlicensed drug mixtures with succeeding generations repeating the mistakes of their predecessors 1,2 . Naïvely, anesthetists may assume that the absence of crystals or of any other changes visible to the naked eye implies compatibility but this is not necessarily the case.…”
Section: Introductionmentioning
confidence: 99%